Pengaruh Peningkatan Kualitas Mobile Banking Terhadap Kepuasan Nasabah Bank BTN Kantor Cabang Pekanbaru - Rahmayanti, Sri; Ilhami, Fidia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
Customer satisfaction in banking will increase along with the increase in mobile banking features at BTN itself The additional features are BPJS payments, PBB payments, PDAM payments, digital wallet top-ups, and virtual accounts for e-commerce transactions. Bank BTN adds a Cardless Withdrawal feature where bank customers can make cardless cash withdrawal transactions at ATMs, as well as QRIS, a feature that makes it easier for customers to make transactions by scanning the QR Code through the BTN Mobile Banking application. Mobile banking has a significant influence on customer satisfaction at Bank BTN Pekanbaru Branch Office. The research was conducted so that banks, especially BTN, can provide the best service from their mobile banking so that they can increase their customers.